Self-supporting Zn-doped p-type copper-based semiconductor photocatalyst and preparation method and application thereof
By introducing Zn ions into the Cu2-xSe photocatalyst and regulating the energy band structure and electronic structure, the effect of efficient CO2 reduction to CH4 of the Cu2-xSe photocatalyst is achieved, and the problem of limited photocatalytic performance in the prior art is solved.
Patent Information
- Application Number
- CN202310604585.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The existing Cu2-xSe photocatalysts have limited photocatalytic performance due to the narrow band gap and the easy recombination of photogenerated carriers, making it difficult to efficiently reduce CO2 to CH4.
Zn ions are introduced through ion doping, the energy band structure and electronic structure of Cu2-xSe are regulated, the utilization rate of photogenerated electrons is improved, and electron conduction is enhanced through the self-supporting structure to achieve high selective reduction of CO2 to CH4.
The photocatalytic activity of Cu2-xSe photocatalyst was improved, and the selectivity of CO2 photocatalytic reduction to CH4 reached 93.84%, and the problem of difficulty in recycling and easy curing of traditional powder catalysts was solved.
Smart Images

Figure CN116984004B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic materials, and in particular relates to a self-supporting Zn-doped p-type copper-based semiconductor photocatalyst and a preparation method and application thereof. Background Art
[0002] As the main traditional energy supply, fossil fuels have limited reserves due to their non-renewable disadvantages. In the process of using fossil fuels, a large amount of carbon dioxide is emitted, leading to climate change. Due to the requirements of sustainable development, the use of fossil fuels and environmental pollution have hindered the development of modern industry. At present, there are chemical, biological, electrochemical and photochemical methods for the conversion of carbon dioxide. Among them, photocatalytic CO2 emission reduction is a research direction for the comprehensive utilization of solar energy, reducing the CO2 content in the atmosphere and producing high value-added products. The element C in CO2 is the highest state, and various C1 and C2 products can be obtained after reduction. The carbon cycle can be achieved by using hydrocarbon fuels as energy carriers. Therefore, in order to realize artificial photosynthesis, the development of efficient photocatalytic materials is a key link, which is also the bottleneck of research and application at this stage.
[0003] Among many semiconductor catalysts, copper-based semiconductors have attracted extensive attention due to their excellent performance and huge reserves. 2-x Se is a typical p-type semiconductor with a narrow energy band gap of about 1.5 eV, which can absorb most of the sunlight and produce electronic transitions. 2-x Se is a copper-deficient compound, and its non-stoichiometric form is more prone to generate vacancies, especially Cu 2-x The microscopic morphology of Se can be regulated according to the synthesis method and conditions, and the petal-shaped biomimetic nanosheet structure can expose as many active sites as possible. This has an important impact on the photocatalytic gas phase reaction. However, due to the narrow band gap, the photogenerated carriers are easy to recombine, and Cu 2-x Se has limitations in its application as a photocatalyst in energy environments. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a self-supporting Zn-doped p-type copper-based semiconductor photocatalyst (Zn-Cu 2-x Se photocatalyst) and its preparation method and application, by ion doping, Zn ions are introduced into Cu 2-x Se crystals, by introducing defects and active sites, regulating their band structure and electronic structure, thereby improving the utilization rate of photogenerated electrons and achieving Cu 2-x The photocatalytic reduction of SeCO2 to CH4 is highly selective. In addition, the in situ growth of the catalyst on the substrate enhances the electron conduction and improves the practicality of the catalyst, while facilitating the catalyst recovery.
[0005] To achieve the above object, the present invention provides a self-supporting Zn-Cu 2-x The preparation method of Se photocatalyst comprises the following steps:
[0006] (1) pre-treating the copper mesh to remove impurities and grease on the surface of the copper mesh;
[0007] (2) Dissolve NaOH, NaBH4 and Se powder in deionized water in turn to prepare Se-containing 2- Solution;
[0008] (3) Dissolve soluble zinc salt in deionized water to prepare Zn 2+ Solution;
[0009] (4) The pretreated copper mesh and the Zn-containing 2+ The solution was added with the Se 2- In the solution, a coprecipitation reaction is carried out;
[0010] (5) After the reaction is completed, cool to room temperature, wash, and dry to obtain a self-supporting Zn-Cu 2-x Se photocatalyst.
[0011] The present invention provides a self-supporting Zn-doped p-type copper-based semiconductor photocatalyst (Zn-Cu 2-x Se photocatalyst), the self-supporting Zn-Cu 2-x Se photocatalyst not only has high photocatalytic activity and high selectivity for photocatalytic reduction of CO2 to CH4 under visible light, but also effectively solves the problems of difficult recycling and easy solidification of traditional powder catalysts.
[0012] Preferably, in step (1), the copper mesh has a size of 5 cm×3 cm×1.5 mm, a wire diameter of 0.1 mm, and a pore size of 100 meshes. The method for pretreating the copper mesh is as follows: cut the commercial copper mesh, and then wash it with acetone, ethanol, and deionized water for 30 minutes respectively to remove impurities and grease on the surface of the copper mesh, and then dry it for use.
[0013] Preferably, in step (2), the mass ratio of NaOH, NaBH4 and Se powder is (1-1.5):(0.05-0.08):(0.05-0.08), and the preferred mass ratio is 1.25:0.07125:0.0075. Under this mass ratio, Se powder can be completely reduced to Se 2- , thus successfully preparing the catalyst.
[0014] Preferably, in step (2), NaOH, NaBH4 and Se powder are dissolved in deionized water in sequence, heated to 60°C, stirred, and heated continuously until the Se powder is completely dissolved to obtain a Se-containing 2- Solution. NaOH was added first to create alkaline conditions for the reduction of Se powder and oxidation of Cu mesh; NaBH4 was used as a reducing agent to reduce Se powder. After changing the order of addition, Se powder was difficult to dissolve, affecting the synthesis of photocatalyst.
[0015] Preferably, in step (3), the soluble zinc salt is Zn(CH3COO)2·2H2O, and the mass ratio of NaOH to Zn(CH3COO)2·2H2O is (1-1.5):0.020-0.146, preferably 1.25:0.020-0.146, and more preferably 1.25:0.103. Within this mass ratio range, the content of doped Zn ions affects the selectivity of CO2 photocatalytic reduction.
[0016] Preferably, in step (4), the pretreated copper mesh is first added to the Se-containing 2- In the solution, add Zn 2+ Solution, first the copper mesh is placed under alkaline conditions to precipitate copper ions and Se 2- Reaction to Cu 2-x Se(0~1); Zn 2+ Add slowly at a rate of 0.1 mL / s to ensure uniform doping.
[0017] The coprecipitation reaction temperature is 90°C for 3 hours under the protection of inert gas, preferably under the protection of nitrogen atmosphere. 2+ with Se 2- reaction, thereby introducing Zn ions into Cu 2-x Se crystal; inert gas protects Cu + A self-supporting Zn-doped p-type copper-based semiconductor photocatalyst prepared according to any of the above preparation methods is denoted as a self-supporting Zn-Cu 2- x Se (x = 0 ~ 1) photocatalyst. The self-supporting Zn-Cu 2-x Application of Se photocatalyst in CO2 photocatalytic reduction.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] The present invention provides a self-supporting Zn-doped in-situ grown Cu 2-xThe invention discloses a preparation method and application of Se / Cu photocatalyst. The invention uses a copper mesh to provide a copper source, NaOH, NaBH4 and Se powder are mixed to provide a selenium source, and Zn(CH3COO)2·2H2O provides a zinc source. The doping of Zn ions is achieved by controlling the coprecipitation method, so as to provide more reaction sites for the reaction, which is beneficial to the adsorption and activation of CO2. Moreover, Zn doping introduces defects and active sites, regulates its energy band structure and electronic structure, thereby improving the utilization rate of photogenerated electrons and achieving Cu 2-x The high selectivity of Se CO2 photocatalytic reduction to CH4. The test results show that the self-supporting Zn-doped in-situ grown Cu prepared by the present invention 2-x Se / Cu photocatalyst material has excellent photocatalytic performance, and the selectivity of CO2 photocatalytic reduction to CH4 is increased to 93.84%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0021] Figure 1 The Cu mesh purchased by the present invention and the self-supporting Cu of comparative example 1 2-x Se catalyst, self-supporting Zn-Cu 2-x XRD pattern of Se photocatalyst;
[0022] Figure 2 The self-supporting Zn-Cu prepared in Example 1 of the present invention 2-x EDS image of Se photocatalyst;
[0023] Figure 3 The self-supporting Zn-Cu prepared in Example 1 of the present invention 2-x SEM image of Se photocatalyst;
[0024] Figure 4 The self-supporting Cu prepared in Comparative Example 1 of the present invention 2-x SEM image of Se photocatalyst;
[0025] Figure 5 A physical diagram of a quartz reactor used in the present invention;
[0026] Figure 6 The self-supporting Zn-Cu prepared in Comparative Examples 1-3 and Example 1 of the present invention 2-x Product generation diagram of CO2 reduction of Se photocatalyst (from left to right are photocatalysts of Comparative Examples 1-3 and Example 1);
[0027] Figure 7 The self-supporting Zn-Cu prepared by different doping ratios in Examples 1-4 of the present invention2-x Product generation diagram of CO2 reduction over Se photocatalyst;
[0028] Figure 8 The self-supporting Zn-Cu prepared in Example 1 of the present invention 2-x Se photocatalyst and the self-supporting Cu 2- x Photoelectric performance diagram of Se catalyst. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] A self-supporting Zn-Cu 2-x The preparation method of Se (x = 0 ~ 1) photocatalyst comprises the following steps:
[0035] (1) Pretreatment of the copper mesh: the copper mesh was cut into 5 cm × 3 cm × 1.5 mm, the wire diameter of the copper mesh was 0.1 mm, and the aperture was 100 mesh. Then, the copper mesh was ultrasonically washed with acetone, ethanol, and deionized water for 30 min in sequence to remove impurities and grease on the surface of the copper mesh, and then dried for later use;
[0036] (2) Dissolve NaOH, NaBH4 and Se powder in deionized water in turn to prepare Se-containing 2- Solution;
[0037] (3) Dissolve soluble zinc salt in deionized water to prepare Zn 2+ Solution;
[0038] (4) First, add the pretreated copper mesh into the Se-containing 2- In the solution, add Zn 2+ The solution was subjected to a coprecipitation reaction at a temperature of 90°C for 3 hours in a nitrogen atmosphere;
[0039] (5) After the reaction is completed, cool to room temperature, wash with deionized water, and dry to obtain a self-supporting Zn-Cu 2-x Se(x=0~1) photocatalyst.
[0040] The present invention uses a simple one-step coprecipitation method to quickly and easily synthesize Zn-doped Zn-Cu 2-x Se nanoflower photocatalyst. This invention provides a unique strategy to 2-x During the self-growth of Se nanoflowers, Zn ions were introduced into Cu 2-x Se crystals, regulating their band structure and electronic structure, inhibiting the recombination of photogenerated carriers, and effectively improving their selectivity for photocatalytic reduction of CO2 to CH4. After Zn ion doping, the specific surface area and vacancies are increased, improving the CO2 in Cu 2-x The adsorption on Se simultaneously promotes electron transfer and accumulation, thereby further protonating the intermediate product to form higher-value CH4, which illustrates the broad application prospects of photocatalysts in environmental protection.
[0041] In the embodiments of the present invention, there is no special limitation on the source of the copper mesh, and a commercial product familiar to those skilled in the art can be used. The copper mesh in the embodiments of the present invention is purchased from Anping County Hangying Wire Mesh Products Co., Ltd. The mesh number of the copper mesh used in the embodiments is preferably 100 meshes, the wire diameter is preferably 0.1 mm, and the size is preferably 5 cm × 3 cm × 1.5 mm.
[0042] In the embodiment of the present invention, when the copper mesh is pretreated, there is no special regulation on the washing reagent (acetone, ethanol and deionized water), and conventional commercial products in the field can be used; a clean copper mesh substrate is obtained by ultrasonic washing, and the ultrasonic frequency is preferably 35 to 55 KHz, and the ultrasonic time is preferably 30 min to 40 min. In the present invention, the drying method is preferably to dry with cold air to make the physical and chemical properties of the copper mesh more stable.
[0043] In an embodiment of the present invention, in step (2), the mass ratio of NaOH, NaBH4 and Se powder is (1-1.5):(0.05-0.08):(0.05-0.08), preferably, NaOH, NaBH4 and Se powder are placed in 50 mL of deionized water in a mass ratio of 1.25:0.07125:0.0075 to prepare a Se-containing 2- Solution.
[0044] In the embodiment of the present invention, in step (2), NaOH, NaBH4 and Se powder are dissolved in deionized water in sequence, heated to 60°C, stirred, and heated continuously until the Se powder is completely dissolved to obtain a Se-containing 2- Solution.
[0045] In an embodiment of the present invention, in step (3), the soluble zinc salt is Zn(CH3COO)2·2H2O, and the mass ratio of NaOH to Zn(CH3COO)2·2H2O is (1-1.5):(0.020-0.146), preferably 0.020-0.146 g Zn(CH3COO)2·2H2O is dissolved in 5 mL of deionized water to prepare a Zn-containing 2+ Solution.
[0046] In the embodiments of the present invention, there is no particular limitation on the sources of Zn(CH3COO)2·2H2O, NaOH, NaBH4 and Se powder, and commercially available products known to those skilled in the art may be used.
[0047] In the embodiment of the present invention, in step (4), the pretreated copper mesh is first added to the Se-containing 2- In the solution, add Zn 2+ Solution;
[0048] The coprecipitation reaction temperature is 90°C, the time is 3 hours, and it is carried out under the protection of inert gas, preferably under the protection of nitrogen atmosphere, so that Zn doping can grow Cu in situ on the copper mesh. 2-x Se.
[0049] A self-supporting Zn-doped p-type copper-based semiconductor photocatalyst prepared according to any of the above preparation methods, denoted as self-supporting Zn-Cu 2-xSe (x=0-1) photocatalyst. In the specific embodiment of the present invention, the copper selenide synthesized from the Cu mesh and the selenium solution is non-stoichiometric, and the non-stoichiometric is not clear, and x can only be in the range of 0-1.
[0050] Application of the self-supporting Zn-doped p-type copper-based semiconductor photocatalyst in CO2 photocatalytic reduction.
[0051] The self-supporting Zn-Cu 2-x Se photocatalyst not only broadens the 2-x The light response range of Se improves the electron utilization rate, avoids the rapid recombination of electrons and holes, and is beneficial to the photocatalytic reduction of CO2. In addition, it also effectively solves the problems of traditional powder catalysts that are difficult to recycle and easy to solidify.
[0052] The present invention is a self-supporting Zn-Cu 2-x There is no special limitation on the use of Se photocatalysts in CO2 photocatalytic reduction, and the catalyst application method familiar to those skilled in the art can be used. 2-x The application of Se in the photocatalytic reduction of CO2 is carried out in a quartz reactor. The actual picture of the quartz reactor is as follows: Figure 5 shown.
[0053] The present invention is a self-supporting Zn-Cu 2-x The test method of Se photocatalyst is not particularly limited, and the catalyst test method familiar to those skilled in the art can be used. In the embodiment of the present invention, gas chromatography is preferably used to test the self-supporting Zn-Cu 2-x Effect of Se photocatalyst on photocatalytic reduction of CO2 There is no special limitation on the gas chromatography measurement operation, and the catalyst test method well known to those skilled in the art can be used.
[0054] The self-supporting Zn-Cu synthesized by the present invention 2-x Se photocatalyst solves the problem of traditional Cu 2-x Problems such as narrow Se band gap, easy recombination of photogenerated carriers and low electron utilization can be solved by doping to adjust the band structure and electron distribution, which is conducive to the generation of other active substances, thereby achieving photocatalytic reduction of CO2.
[0055] The technical solution of the present invention is fully and clearly described below in conjunction with embodiments.
[0056] Example 1
[0057] (1) A copper mesh with a specification of 100 mesh and a wire diameter of 0.1 mm was cut into a size of 5 cm × 3 cm × 1.5 mm, and ultrasonically cleaned (frequency: 55 kHz) with acetone, ethanol, and deionized water for 30 min, and then naturally air-dried;
[0058] (2) Dissolve 1.25 g NaOH, 0.07125 g NaBH4 and 0.0075 g Se powder in 50 mL deionized water, heat to 60 °C and stir to dissolve. Continue heating for 1 h until the Se powder is completely dissolved. Prepare a Se-containing 2- Solution;
[0059] (3) Dissolve 0.020 g Zn(CH3COO)2·2H2O in 5 mL deionized water to prepare a Zn-containing 2+ Solution;
[0060] (4) Place the copper mesh treated in step (1) on a Se-containing 2- In the solution, Zn 2+ The solution was placed at 90 °C in a nitrogen atmosphere for 3 h to obtain a self-supporting Zn-Cu 2-x Se (x = 0 ~ 1) photocatalyst, denoted as 1-Zn-Cu 2-x Se.
[0061] Comparative Example 1
[0062] (1) A copper mesh with a specification of 100 mesh and a wire diameter of 0.1 mm was cut into a size of 5 cm × 3 cm × 1.5 mm, and ultrasonically cleaned (frequency: 55 kHz) with acetone, ethanol, and deionized water for 30 min, and then naturally air-dried;
[0063] (2) Dissolve 1.25 g NaOH, 0.07125 g NaBH4 and 0.0075 g Se powder in 50 mL deionized water, heat to 60 °C and stir to dissolve. Continue heating for 1 h until the Se powder is completely dissolved to prepare a Se-containing 2- Solution;
[0064] (3) Place the copper mesh treated in step (1) on a Se-containing 2- The solution was placed at room temperature (25°C) in a nitrogen atmosphere for 3 h to obtain a self-supporting Cu 2-x Se (x = 0 ~ 1) catalyst.
[0065] Figure 1 The Cu mesh purchased by the present invention and the self-supporting Cu of comparative example 1 2-x Se catalyst, self-supporting Zn-Cu 2-x The XRD pattern of Se photocatalyst shows that the self-supporting in-situ grown Zn-Cu 2-xSe photocatalyst.
[0066] Figure 2 The self-supporting Zn-Cu prepared in Example 1 2-x The EDS image of Se photocatalyst shows the content of four elements: Cu, Se, Zn and O.
[0067] Figure 3 The self-supporting Zn-Cu prepared in Example 1 2-x SEM image of Se photocatalyst, Figure 4 The self-supporting Cu prepared in Comparative Example 1 2-x From the SEM images of the Se photocatalyst, it can be seen that the samples all present a flower ball structure, but it can be clearly seen that the self-supporting Zn-Cu 2-x Se photocatalyst morphology comparison with Cu 2-x The morphology of Se (x=0-1) is rougher, so the photocatalyst prepared in Example 1 of the present invention has more active sites, which is more conducive to the adsorption and activation of CO2.
[0068] Example 2
[0069] (1) A copper mesh with a specification of 100 mesh and a wire diameter of 0.1 mm was cut into a size of 5 cm × 3 cm × 1.5 mm, and ultrasonically cleaned (frequency: 35 kHz) with acetone, ethanol, and deionized water for 40 min, and then naturally air-dried;
[0070] (2) Dissolve 1.25 g NaOH, 0.07125 g NaBH4 and 0.0075 g Se powder in 50 mL deionized water, heat to 60 °C and stir to dissolve. Continue heating for 1 h until the Se powder is completely dissolved to prepare a Se-containing 2- Solution;
[0071] (3) Dissolve 0.061 g Zn(CH3COO)2·2H2O in 5 mL deionized water to prepare a Zn-containing 2+ Solution;
[0072] (4) Place the copper mesh treated in step (1) on a Se-containing 2- In the solution, Zn 2+ The solution was placed at 90 °C in a nitrogen atmosphere for 3 h to obtain a self-supporting Zn-Cu 2-x Se (x = 0 ~ 1) photocatalyst, denoted as 2-Zn-Cu 2-x Se.
[0073] Example 3
[0074] (1) A copper mesh with a specification of 100 mesh and a wire diameter of 0.1 mm was cut into a size of 5 cm × 3 cm × 1.5 mm, and ultrasonically cleaned (frequency: 40 kHz) with acetone, ethanol, and deionized water for 30 min, and then naturally air-dried;
[0075] (2) Dissolve 1.25 g NaOH, 0.07125 g NaBH4 and 0.0075 g Se powder in 50 mL deionized water, heat to 60 °C and stir to dissolve. Continue heating for 1 h until the Se powder is completely dissolved to prepare a Se-containing 2- Solution;
[0076] (3) Dissolve 0.103 g Zn(CH3COO)2·2H2O in 5 mL deionized water to prepare a Zn-containing 2+ Solution;
[0077] (4) Place the copper mesh treated in step (1) on a Se-containing 2- In the solution, Zn 2+ The solution was placed at 90 °C in a nitrogen atmosphere for 3 h to obtain a self-supporting Zn-Cu 2-x Se (x = 0 ~ 1) photocatalyst, denoted as 3-Zn-Cu 2-x Se.
[0078] Example 4
[0079] (1) A copper mesh with a specification of 100 mesh and a wire diameter of 0.1 mm was cut into a size of 5 cm × 3 cm × 1.5 mm, and ultrasonically cleaned (frequency: 40 kHz) with acetone, ethanol, and deionized water for 30 min, and then naturally air-dried;
[0080] (2) Dissolve 1.25 g NaOH, 0.07125 g NaBH4 and 0.0075 g Se powder in 50 mL deionized water, heat to 60 °C and stir to dissolve. Continue heating for 1 h until the Se powder is completely dissolved to prepare a Se-containing 2- Solution;
[0081] (3) Dissolve 0.146 g Zn(CH3COO)2·2H2O in 5 mL deionized water to prepare a Zn-containing 2+ Solution;
[0082] (4) Place the copper mesh treated in step (1) on a Se-containing 2- In the solution, Zn 2+ The solution was placed at 90 °C in a nitrogen atmosphere for 3 h to obtain a self-supporting Zn-Cu 2-x Se (x = 0 ~ 1) photocatalyst, denoted as 4-Zn-Cu 2-x Se.
[0083] Comparative Example 2 (changing temperature)
[0084] The same as Example 1, except that step (4) is: placing the copper mesh treated in step (1) on a Se-containing 2- In the solution, Zn 2+ The solution was allowed to stand at room temperature (25°C) under nitrogen atmosphere for 3 hours to obtain a photocatalyst.
[0085] Comparative Example 3 (Changing the order of adding materials in step (2))
[0086] The same as Example 1, except that step (2) is as follows: 0.0075 g of Se powder, 1.25 g of NaOH and 0.07125 g of NaBH4 are dissolved in 50 mL of deionized water, heated to 60 ° C and stirred to dissolve, and heated for 1 h until the Se powder is completely dissolved to prepare a Se-containing 2- Solution.
[0087] Application Example 1
[0088] The 7 photocatalyst materials prepared in Examples 1-4 and Comparative Examples 1-3 were used to test the photocatalytic reduction efficiency of the catalysts for CO2 using a gas chromatograph. A xenon lamp was used to simulate sunlight conditions, and the catalysts were placed in a 450 mL quartz reactor ( Figure 5 ) was introduced with 80 kPa CO2, and the actual contact area of the catalyst was 15 cm 2 , and then connect the quartz reactor to a gas chromatograph (GC). During the test reaction, a sample was taken every 1 hour to detect the product concentration in the reactor and calculate the selectivity of the product conversion. Finally, a CO2 photoreduction product generation diagram was drawn as shown in Figure 6 and Figure 7 shown.
[0089] from Figure 6 It can be seen that the photocatalysts prepared in Example 1 and Comparative Examples 1-3 of the present invention have better photocatalytic performance than other catalysts in terms of the yield and selectivity of CO2 photocatalytic reduction. 2+ After doping, the selectivity of photocatalytic reduction to CH4 is improved; compared with comparative examples 2-3, under appropriate reaction conditions, the catalyst is successfully synthesized with excellent performance.
[0090] from Figure 7 It can be seen that the photocatalysts prepared in Examples 1-4 of the present invention have higher yield and selectivity in the CO2 photocatalytic reduction reaction in Example 3 at different doping mass ratios, indicating that appropriate doping can significantly improve the performance of the photocatalyst.
[0091] Application Example 2
[0092] The two photocatalyst materials prepared in Example 1 and Comparative Example 1 were also used to test the photocurrent response using an electrochemical workstation, and the photoelectric performance was finally obtained by plotting: Figure 8 shown.
[0093] from Figure 8 It can be seen that the self-supporting Zn-doped in-situ grown Cu 2-x Se / Cu photocatalyst has better photoelectric performance and can inhibit the recombination of photogenerated carriers, indicating that the photocatalyst has excellent photocatalytic performance.
[0094] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a self-supporting Zn-doped p-type copper-based semiconductor photocatalyst for CO2 photocatalytic reduction, characterized in that: The following steps are involved: (1) pre-treating the copper mesh to remove impurities and grease on the surface of the copper mesh; (2) Dissolve NaOH, NaBH4 and Se powder in deionized water in turn to prepare Se-containing 2- Solution; (3) Dissolve soluble zinc salt in deionized water to prepare Zn 2+ Solution; (4) The pretreated copper mesh and the Zn-containing 2+ The solution was added with the Se 2- The coprecipitation reaction was carried out in the solution at a temperature of 90°C for 3 hours under the protection of inert gas; (5) After the reaction is completed, the reaction is cooled to room temperature, cleaned, and dried to obtain a self-supporting Zn-doped p-type copper-based semiconductor photocatalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the copper mesh has a size of 5 cm × 3 cm × 1.5 mm, a wire diameter of 0.1 mm, and a pore size of 100 meshes.
3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of NaOH, NaBH4 and Se powder is (1-1.5):(0.05-0.08):(0.05-0.08).
4. The preparation method according to claim 1, characterized in that: In step (2), NaOH, NaBH4 and Se powder are dissolved in deionized water in sequence, heated to 60°C, stirred, and heated continuously until the Se powder is completely dissolved to obtain a Se-containing 2- Solution.
5. The preparation method according to claim 1, characterized in that: The soluble zinc salt is Zn(CH3COO)2·2H2O, and the mass ratio of NaOH to Zn(CH3COO)2·2H2O is (1-1.5):(0.020-0.146).
6. The preparation method according to claim 1, characterized in that: In step (4), the pretreated copper mesh is first added to the Se-containing 2- In the solution, add Zn 2+ Solution.
7. A self-supporting Zn-doped p-type copper-based semiconductor photocatalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the self-supporting Zn-doped p-type copper-based semiconductor photocatalyst according to claim 7 in CO2 photocatalytic reduction.
